2019
DOI: 10.1002/acm2.12763
|View full text |Cite
|
Sign up to set email alerts
|

A study of nonuniform CTV to PTV margin expansion incorporating both rotational and translational uncertainties

Abstract: PurposeIn this work, we implemented a method to obtain a nonuniform clinical target volume (CTV) to planning target volume (PTV) margin caused by both rotational and translational uncertainties and evaluated it in the treatment planning system (TPS).Materials and methodBased on a previously published statistical model, the relationship between a target margin and the distance d (from isocenter to target point), setup uncertainties, and significance level was established. For a single CTV, it can be thought as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
1
21
0
Order By: Relevance
“…This consideration will probably affect the V 12Gy and the OAR doses but to compare strictly the two techniques, the present study was performed without margin. The margin used on a linac for a mono-isocentric technique can be of 0, 1, 2 mm or even non-uniform [ 23 ] depending on the distance from the isocenter and the repositionning tolerance. Considering the possibilities in GP, it's also possible to add margins so we cannot exclude that some groups use a margin on the GP.…”
Section: Discussionmentioning
confidence: 99%
“…This consideration will probably affect the V 12Gy and the OAR doses but to compare strictly the two techniques, the present study was performed without margin. The margin used on a linac for a mono-isocentric technique can be of 0, 1, 2 mm or even non-uniform [ 23 ] depending on the distance from the isocenter and the repositionning tolerance. Considering the possibilities in GP, it's also possible to add margins so we cannot exclude that some groups use a margin on the GP.…”
Section: Discussionmentioning
confidence: 99%
“…One problem is how to manage the rotational uncertainties of the patient setup. Many studies (12)(13)(14)(15) have focused on this problem and provided advice to address it. Faught AM et al (13) suggested that clinical medical physicists revisit the quality assurance tolerances of gantry and multi-leaf collimator (MLC) angles.…”
Section: Introductionmentioning
confidence: 99%
“…Faught AM et al (13) suggested that clinical medical physicists revisit the quality assurance tolerances of gantry and multi-leaf collimator (MLC) angles. Miao J et al (15) proposed the method of expanding the nonuniform gross target volume (GTV) or clinical target volume by adding a planning target volume (PTV) margin. The other problem is how to reduce unnecessary exposure of normal brain tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations